Iridium Alloy

The Iridium alloy with controlled platinum and tantalum content addresses durability issues by enhancing oxidation resistance and recrystallization temperature, ensuring stable performance in high-temperature applications.

JP7624365B2Active Publication Date: 2025-01-30DENSO CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021134663
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-08-20
Publication Date
2025-01-30
Estimated Expiration
2041-08-20

AI Technical Summary

Technical Problem

Existing Iridium alloys are insufficient in durability to meet the demands of high-power ignition plugs and other applications requiring high-temperature resistance and corrosion resistance.

Method used

An Iridium alloy containing specific ranges of platinum (5-30 mass%) and tantalum (0.3-5 mass%) enhances durability by suppressing oxidation and improving recrystallization temperature, while maintaining processability.

Benefits of technology

The alloy exhibits improved oxidation resistance, recrystallization temperature, and mechanical strength, enabling stable operation in high-temperature environments and facilitating easy processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007624365000001
    Figure 0007624365000001
Patent Text Reader

Abstract

To provide an iridium alloy with high durability.SOLUTION: An iridium alloy contains iridium, platinum, and tantalum, a content of platinum being 5 wt.% to 30 wt.% and a content of tantalum being 0.3 wt.% to 5 wt.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to iridium alloys. [Background technology]

[0002] Iridium alloys, which contain iridium and, for example, platinum, are known as materials with excellent heat resistance and corrosion resistance, and are used in various fields. For example, the following Patent Document 1 describes that by containing a predetermined amount of platinum and a predetermined amount of an alkaline earth metal element in an iridium alloy, the iridium alloy can be stably used for a long period of time in a high-temperature environment. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-138418 A Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, the demand for durability of iridium alloys has been getting higher. For example, in the field of spark plugs, spark plugs are becoming higher current and voltage in order to increase the power output of internal combustion engines and improve fuel efficiency. For this reason, the iridium alloys used as the material for the discharge parts are being required to have a higher level of durability than before, and the iridium alloys described in the above patent documents may not be able to meet this demand in the future. It is considered that the level of durability required of iridium alloys will become higher in the future in fields other than spark plugs as well.

[0005] The present disclosure aims to provide an iridium alloy that is highly durable. [Means for solving the problem]

[0006] The iridium alloy according to the present disclosure is an iridium alloy containing iridium, platinum, and tantalum, and the platinum content is 5. quality % to 30 quality %, with a tantalum content of 0.3 quality % to 5 quality % range.

[0007] In the iridium alloy having the above composition, by setting the platinum and tantalum contents within the above ranges, it is possible to improve durability when exposed to a high-temperature oxidizing atmosphere (for example, air) compared to conventional ones. Effect of the Invention

[0008] In accordance with the present disclosure, a highly durable iridium alloy is provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The present embodiment will be described below.

[0010] The iridium alloy according to the first embodiment contains a predetermined amount of platinum (Pt) and a predetermined amount of tantalum (Ta) relative to iridium (Ir). The platinum content in the iridium alloy is 5 quality % to 30 quality The tantalum content in the iridium alloy is preferably within the range of 0.3 quality % to 5 quality % is preferable.

[0011] When an iridium alloy contains platinum, the oxidation and volatilization of iridium from the grain boundaries is suppressed when the iridium alloy is exposed to a high-temperature oxidizing atmosphere (e.g., air), and as a result, the oxidation and wear resistance of the iridium alloy is significantly improved. quality The present inventors have confirmed that if the content is less than 5%, the above-mentioned effects are not sufficiently exhibited.

[0012] On the other hand, the platinum content in iridium alloys is increased to 30 quality %, the oxidation consumption resistance of the iridium alloy is further improved, but in this case, both the melting point and recrystallization temperature of the iridium alloy are lowered, lowering the upper limit of the temperature range in which the iridium alloy can be stably used.

[0013] For the above reasons, in the iridium alloy according to the present embodiment, the platinum content is set to 5.0 or less as described above. quality % to 30 quality It is stipulated that the range is up to %.

[0014] When tantalum is added to an iridium alloy, the strength is improved by solution hardening. The recrystallization temperature also increases. Since the recrystallization temperature of the iridium alloy increases, the fine structure of the iridium alloy is maintained even at high temperatures, and the crystal grains are less likely to fall off. In addition, the increase in recrystallization temperature suppresses the softening of the iridium alloy at high temperatures. As a result, the durability of the iridium alloy is improved. In addition, when the tantalum content in the iridium alloy is 0.3 quality The present inventors have confirmed that if the content is less than 5%, the above-mentioned effects are not sufficiently exhibited.

[0015] On the other hand, if the tantalum content in the iridium alloy is increased to 5 quality %, the density of the iridium alloy decreases. For this reason, the inventors have confirmed that, for example, when the discharge portion of an ignition plug is made of the iridium alloy, the wear resistance due to spark discharge decreases. In addition, when the tantalum content in the iridium alloy is increased to more than 5%, the density of the iridium alloy decreases. quality %, the iridium alloy undergoes excessive solution hardening, resulting in a decrease in plastic deformability and making it difficult to process the iridium alloy. Furthermore, other elements contained in the iridium alloy (e.g., cobalt and nickel, which will be described later) are more likely to oxidize, resulting in a decrease in oxidation wear resistance.

[0016] For the above reasons, in the iridium alloy according to the present embodiment, the tantalum content is set to 0.3 as described above. quality % to 5 quality The tantalum content in iridium alloys is limited to 0.5%. quality It is more preferable to set it to 0.7% or more. quality The present inventors have confirmed that it is even more preferable to set the content to 50% or more.

[0017] As a second embodiment, the iridium alloy according to the first embodiment may further contain an additive material composed of either one or both of cobalt and nickel in a form replacing a part of the iridium. The additive material may be a material containing only cobalt element, a material containing only nickel element, or a material in which cobalt element and nickel element are mixed in any ratio. In any case, the content of the additive material in the iridium alloy is 1.5 quality % is preferable.

[0018] For iridium alloys containing iridium, platinum, and tantalum, the above additive materials are added at 1.5 quality %, the above-mentioned solid solution hardening is promoted, and the strength can be further improved. Furthermore, when the iridium alloy is exposed to a high-temperature oxidizing atmosphere (for example, air at 1200°C or higher), oxides of the above-mentioned additive materials are generated and distributed at the grain boundaries of the iridium alloy. These oxides function as protective materials, suppressing the outward diffusion of iridium and the subsequent oxidative volatilization, and therefore the oxidation wear resistance of the iridium alloy is further improved.

[0019] On the other hand, the content of the above additive materials in the iridium alloy is 1.5 qualityThe inventors have confirmed that if the content of the additive is greater than 1%, the oxides of the additive materials are generated in excess, and the oxidation wear resistance of the iridium alloy is reduced. In this case, the melting point of the iridium alloy is lowered, and the upper limit of the temperature range in which the iridium alloy can be stably used is lowered.

[0020] For the above reasons, in the iridium alloy according to the present embodiment, the content of the above-mentioned additive material is set to 1.5, as described above. quality It is stipulated that the range is up to %.

[0021] In addition, the content of the above additive materials in the iridium alloy is 1.5 quality %, if the total content of tantalum and the content of the above additive materials is within 5 quality The inventors have confirmed that if the content of tantalum exceeds 5%, the workability of the iridium alloy decreases. This is believed to be due to the work hardening caused by the addition of tantalum being excessively promoted by the above-mentioned additive materials. Therefore, the total content of tantalum and the above-mentioned additive materials in the iridium alloy should be less than 5. quality % is preferable.

[0022] In any of the above embodiments, the iridium alloy is a single-phase solid solution without a second phase. Therefore, it has good malleability and can be plastically worked into various shapes and sizes using known working methods (e.g., warm working, hot working, etc.). In addition, it can be easily machined and welded. EXAMPLES

[0023] The inventors prepared test pieces of a number of iridium alloys included in each of the above embodiments as "Examples", and prepared test pieces of a number of iridium alloys not included in each of the above embodiments as "Comparative Examples", and evaluated each of them. Table 1 shows parameters such as density and evaluation results such as workability for each test piece. [Table 1]

[0024] In the "Number" column in Table 1, a unique number corresponding to each test piece is shown. The examples are numbered from 1 to 32, and the comparative examples are numbered from 1 to 6. In the "Density" column in Table 1, the density of each test piece is shown in "g / cm 3 The "Content" column in Table 1 shows the content of iridium (Ir), platinum (Pt), tantalum (Ta), nickel (Ni), and cobalt (Co) in each test piece, respectively. quality The total amount of nickel and cobalt in these materials falls under the category of "additive materials" mentioned above.

[0025] <Method of preparing test pieces> Iridium powder, platinum powder, tantalum powder, nickel powder, and cobalt powder were prepared to prepare each of the test pieces shown in Table 1. These material powders were then mixed in a ratio corresponding to each test piece to prepare a mixed powder.

[0026] Then, each mixed powder was molded into a green compact using a uniaxial press, and the green compact obtained was melted by an arc melting method to create an ingot that was the basis of each test piece. Next, each ingot was hot forged at a high temperature of 1500°C or higher to form a square bar with a width of 15 mm, and each square bar was processed into a wire rod with a diameter of 0.5 mm to form the test piece. The processing from the square bar to the wire rod was performed by groove rolling the square bar in a temperature environment of 1000°C to 1400°C, and then performing a die wire drawing process.

[0027] After preparing a plurality of test pieces by the above-mentioned method, the inventors carried out various evaluations on each of the test pieces. The columns of "workability," "solidus point," "oxidation wear resistance," "recrystallization temperature," "high temperature strength," and "overall evaluation" in Table 1 show the evaluation results of each test piece. Details of the evaluation method for each item are as follows.

[0028] <Method of evaluating workability> Workability was evaluated based on whether or not the square bars could be processed into wire as described above. If cracks occurred during processing and wire could not be obtained, the workability was evaluated as "x", and otherwise, if wire was obtained, the workability was evaluated as "good". Note that for those samples where the workability was evaluated as "x", no test pieces could be obtained, so no evaluation was performed on items other than workability.

[0029] <Method of evaluating solidus point> Each test piece was heated to 2100°C in an argon atmosphere in an electric furnace, and the appearance and cross section were visually observed before and after the heating. Those that showed no change in appearance or cross section were presumed to have a solidus point of 2100°C or higher and were evaluated as "Good." Those that showed traces of melting in the appearance and cross section were presumed to have a solidus point of less than 2100°C and were evaluated as "Poor."

[0030] <Evaluation method for oxidation wear resistance> Each test piece was cut to a length of 0.8 mm, heated in an electric furnace, and held at the specified temperature for 20 hours. Heating in the electric furnace was carried out in an air atmosphere. The test was carried out at two specified temperatures, 1000°C and 1200°C. The surface area of ​​the test piece before heating was S (unit: mm 2 ), the mass of the test piece before heating is M0 (unit: mg), and the mass of the test piece after heating is M1 (unit: mg), the mass change ΔM (unit: mg / mm) is calculated by the formula ΔM = (M1 - M0) / S. 2 ) was used as an index showing the oxidation wear resistance of each test piece. The surface area S (mm 2 ) was calculated from the dimensions of the test piece.

[0031] Regarding the resistance to oxidation and wear when heated to 1000°C, if the ΔM value was -0.25 or more, it was evaluated as "◎" (particularly good), and if the ΔM value was less than -0.25, it was evaluated as "◯" (good).

[0032] Regarding the resistance to oxidation and wear when heated to 1200°C, if the ΔM value was -0.35 or more, it was rated as "◎" (particularly good), and if the ΔM value was less than -0.35, it was rated as "◯" (good).

[0033] <Method of evaluating recrystallization temperature> Each test piece was subjected to a heat treatment in which it was heated to a specified temperature, and the temperature at which recrystallization occurred (i.e., the recrystallization temperature) was measured for each test piece by checking whether recrystallization occurred after the heat treatment. Test pieces whose recrystallization temperature exceeded 1150°C were evaluated as "◎", those whose recrystallization temperature exceeded 1050°C and was equal to or lower than 1150°C were evaluated as "◯", and those whose recrystallization temperature was equal to or lower than 1050°C were evaluated as "△".

[0034] <Method of evaluating high-temperature strength> The evaluation of high-temperature strength was performed based on the tensile strength (tensile strength) value obtained by performing a tensile test on each test piece at high temperature. Note that, instead of the test pieces of wire rod described above, test pieces cut from plate material of the same material by wire electric discharge machining were used as the test pieces to be subjected to the tensile test. The test pieces were cut so that the cross section of the parallel part was a square of 0.5 mm x 0.5 mm and the length of the parallel part was 3 mm. The tensile test was performed under the conditions of a test piece temperature of 1200°C, in an air atmosphere, and a crosshead speed of 5 mm / min. The measured values ​​of high-temperature strength shown in Table 1 are the obtained tensile strength values ​​in units of "MPa".

[0035] With regard to high temperature strength, those whose measured tensile strength exceeded 550 MPa were rated as "◎", those whose tensile strength exceeded 250 MPa and was 550 MPa or less were rated as "◯", and those whose tensile strength was 250 MPa or less were rated as "△".

[0036] <Overall evaluation> Of the above evaluation items, the three items of oxidation wear resistance, recrystallization temperature, and high-temperature strength were evaluated comprehensively. Items rated as "◎" were given 3 points, items rated as "〇" were given 2 points, items rated as "△" were given 1 point, and items rated as "×" were given 0 points, and an overall evaluation was performed based on the total points of each evaluation item. Test pieces with a total score of 12 were given an overall evaluation of "A," test pieces with a total score of 9 to 11 were given an overall evaluation of "B," and test pieces with a total score of 8 or less were given an overall evaluation of "C." Test pieces with a workability rating of "×" were given an overall evaluation of "D."

[0037] As shown in Table 1, the test pieces of the Examples were all given an overall rating of A or B, and were confirmed to be excellent iridium alloys with high durability. On the other hand, the test pieces of the Comparative Examples were all given an overall rating of C or D, and were confirmed to be inferior in durability and workability compared to the Examples.

[0038] As shown in Table 1, the density of each of the test pieces in the examples was 21.5 g / cm 3 By setting the contents of iridium, platinum, tantalum, and the above-mentioned additive materials in the iridium alloy within the ranges described above, the preferred density range is 21.5 g / cm 3 Even when the contents of the above elements are changed within the ranges of the first and second embodiments to produce examples different from those shown in Table 1, the iridium alloys with sufficient durability have a density of 21.5 g / cm 3 The present inventors have confirmed that this is the case.

[0039] The present embodiment has been described above with reference to specific examples. However, the present disclosure is not limited to these specific examples. Any design modifications made by a person skilled in the art to these specific examples are also included within the scope of the present disclosure as long as they have the features of the present disclosure. The elements of each of the above-mentioned specific examples and their arrangements, conditions, shapes, etc. are not limited to those exemplified and can be changed as appropriate. The combination of each of the elements of each of the above-mentioned specific examples can be changed as appropriate as long as no technical contradiction occurs.

Claims

1. An iridium alloy consisting of iridium, platinum, and tantalum and unavoidable impurities, The platinum content is within the range of 5% by mass to 30% by mass, 1. An iridium alloy, wherein the tantalum content is in the range of 0.3% to 5% by weight.

2. Further comprising an additive material consisting of either or both of the elements cobalt and nickel, 2. The iridium alloy of claim 1, wherein the content of said additive material is in the range of up to 1.5% by weight.

3. 3. The iridium alloy of claim 2, wherein the sum of the tantalum content and the additive material content is in the range of up to 5% by weight.

Citation Information

Patent Citations

  • Novel platinum alloy electrical contact material and preparation method thereof

    CN101948965A

  • Iridium base alloy

    JP1998259435A

  • alloy

    JP2005533924A

  • HEAT RESISTANT Ir BASE ALLOY

    JP2008248322A

  • spark plug

    JP2009531813A